The effects of combined micron-/submicron-scale surface roughness and nanoscale features on cell proliferation and differentiation - Gittens I, Rolando A. (2011)
Titanium (Ti) osseointegration is critical for the success of dental and orthopaedic implants. Previous studies have shown that surface roughness at the micro- and submicro-scales promotes osseointegration by enhancing osteoblast differentiation and local factor production. Only relatively recently have the effects of nanoscale roughness on cell response been considered. The aim of the present study was to develop a simple and scalable surface modification treatment that introduces nanoscale features to the surfaces of Ti substrates without greatly affecting other surface features, and to determine the effects of such superimposed nano-features on the differentiation and local factor production of osteoblasts. A simple oxidation treatment was developed for generating controlled nanoscale topographies on Ti surfaces, while retaining the starting micro-/submicro-scale roughness. Such nano-modified surfaces also possessed similar elemental compositions, and exhibited similar contact angles, as the original surfaces, but possessed a different surface crystal structure. MG63 cells were seeded on machined (PT), nano-modified PT (NMPT), sandblasted/acid-etched (SLA), and nano-modified SLA (NMSLA) Ti disks. The results suggested that the introduction of such nanoscale structures in combination with micro-/submicro-scale roughness improves osteoblast differentiation and local factor production, which, in turn, indicates the potential for improved implant osseointegration in vivo.